Proposal for initial management of uncomplicated ST elevation myocardial infarction in centers without percutaneous coronary intervention capacity in Peru - Custodio-Sánchez, Piero (2023)
ST-segment elevation myocardial infarction (STEMI) is a clinical entity whose adequate treatment will depend on its prompt recognition, accurate diagnosis, and management in reperfusion networks. The first contact with these patients is generally done in centers without reperfusion capacity, attended by non-cardiologist doctors, and in centers far from hospitals with greater resolution capacity, something that is well known in our country. This manuscript proposes a strategy for the diagnosis and treatment of STEMI in centers without percutaneous coronary intervention capacity of the public health system in Peru, emphasizing not losing sight of electrocardiographic patterns compatible with coronary artery occlusion, adequate fibrinolysis and management of its complications, the treatment of infarction in special populations and highlighting the importance of the pharmacoinvasive strategy as the main form of reperfusion treatment in our country.